Long-Term Anticoagulation in Secondary Ischemic Stroke Prevention: The Prospective Multicenter RESTAIC Registry - Gutiérrez-Zúñiga, Raquel (Front Neurol, 2020)
Background and Objective: Oral anticoagulation (OAC) for secondary stroke prevention is recommended in atrial fibrillation (AF) and other sources of cardioembolic stroke. Our objectives were to explore the differences in ischemic and hemorrhagic events when using OAC for secondary stroke prevention according to the type of anticoagulant treatment and to analyze the number and reasons for OAC switches during long-term follow-up. Methods: Ischemic stroke (IS) patients who were discharged on OAC for secondary stroke prevention from January 2014 to October 2017 were recruited in a prospective, multicenter, hospital-based registry. Follow-up at 3 months was scheduled at the outpatient clinic with subsequent annual phone interviews for 3 years. Patients were classified into three study groups according to OAC at discharge: Vitamin K antagonist (VKA), Factor Xa inhibitor (FXa), or direct thrombin inhibitor (DTI). We compared stroke recurrences, intracranial hemorrhage, major bleeding, and all-cause mortality during the follow-up. We recorded any switches in OAC and the main reasons for the change. Results: A total of 241 patients were included. An anticoagulant was indicated in the presence of a source of cardioembolic stroke in 240 patients (99.6%) and lupus plus antiphospholipid syndrome in one patient. Up to 86 patients (35.6%) were on OAC before the index stroke; in 71 (82.5%) of them, this was VKA. At hospital discharge, 105 were treated with FXa (43.8%), 96 with VKA (39.6%), and 40 with DTI (16.6%). The cumulative incidences at 3 years were 17% for stroke recurrence, 1.6% for intracranial hemorrhage, 4.9% for major hemorrhage, and 22.8% for all-cause mortality, with no differences among the OAC groups in any outcomes. During the follow-up, 40 OAC switches were recorded (63% of them to FXa), mostly due to stroke recurrence. Conclusion: Long-term OAC in secondary stroke prevention is associated with a lower frequency of bleeding complications than stroke recurrences. No differences between anticoagulant drugs were found in any of the analyzed outcomes. The main cause for OAC switch during follow-up was stroke recurrence.